Implementing the Quality Function to Improve the Organic Vegetable Quality - Yuanita, Maulina; Sutanto, Adi (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2023)
This research delves into the pivotal role of quality management in sustaining organic vegetable production, underscoring its profound connection to consumer satisfaction and subsequent impact on purchasing decisions. Within the organic market, predominantly catering to the upper to middle-class demographic in Batu, East Java, Indonesia, consumer preferences dictate heightened product specifications and, consequently, necessitate a focus on quality. To fortify market presence, this study advocates for the direct involvement of organic farmers throughout the entire production-to-marketing continuum, transforming them into not just cultivators but entrepreneurs. In the face of escalating competition, product quality emerges as a paramount subsystem requiring prioritization. The study employs the quality function method for planning and developing pertinent organic vegetable products aligned with consumer interests, identifying areas for improvement. The primary objective is to ascertain consumer demands and devise corrective measures to augment satisfaction. Employing the online survey method, participants were limited to consumers who had purchased organic vegetable products from Batu-based farmers in East Java at least twice. Analyzing the data revealed that consumer prioritized quality attributes encompassed vegetable cleanliness, product pricing, and ease of accessibility. Notably, technical interventions such as the implementation of Good Handling Practices, Internal Control System (ICS), and enhancing service quality during organic vegetable cultivation significantly influenced consumer interest attributes, fostering heightened satisfaction. This study contributes valuable insights for organic farmers and stakeholders seeking to optimize product quality in response to evolving consumer demands.